Effect of Perceived Fairness in Pay System on Work-Related Attitudes - Ismail, Azman; Abdin, Fatmawati; Muhamad, Nur Sa’adah; Mohamad Nor, Azmawaty (UUM Press, 2020)
Perceived fairness in pay system has two critical features, namely procedural fairness and distributive fairness. Recent studies have shown that the capability of employers to propose and administer pay systems appropriately, including allocating pay and determining the value of pay in a fair manner, has a positive association with employees' work-related attitude. Although this association has been well-researched, the role of perceived fairness as a vital predicting variable of work-related attitude, particularly towards job satisfaction and organizational commitment, has still not been thoroughly deliberated. Hence, this study fills this gap. Self-report survey questionnaires were collected from the employees of a public audit agency in Peninsular Malaysia. Smart PLS software was utilized to assess the quality of the research instrument and test the research hypotheses. The results of hypothesis testing confirm that perceived procedural fairness and distributive fairness in managing the pay system, are important determinants of job satisfaction and organizational commitment in the examined organization. Additionally, this study offers useful guidelines for practitioners to improve the pay management system and proposes future studies.